Parâmetros genéticos dos teores de proteína e de fibra alimentar associados ao rendimento de grãos em feijão - Londero, Patricia Medianeira Grigoletto (2005)
Common bean cultivars development with high nutritional quality joined with grain yield is desirable. In consequence, of this study evaluated the genitors, F1 and its reciprocals, F2 and backcrosses populations obtained in the combination among four genitors. For protein content were used TPS Nobre, Guapo Brilhante, BRS Expedito and UTF-1 Balisa. For fibers content, CNFP 8100, FT 96-1282, Valente and Varre Sai were used. The crossings were performed inside a greenhouse using complete diallel approach and assessed in the field using a randomized complete block design with two replications. The laboratory analyses were realized to protein and dietary fiber content. Negative phenotypic correlation between protein content and grain yield was observed. The crossings between the high protein content genitors produced F2 populations with high protein content. Genetic variability was observed for genitors, F1 s and their reciprocals for dietary fiber content. The largest heritability estimates were obtained for fibers content and the smallest for grain yield. Phenotypic correlation between dietary fiber, their different fractions (soluble and insoluble) and grain yield was not observed. Phenotypic correlation between fiber insoluble and dietary fiber content was positive, wile between soluble and insoluble fiber was negative. In the populations studied, the selection for protein content and fibers associated with high grain yield could be performed with success as long as we have better understanding of the genetic control, environmental effect and genotype x environment interaction that influence these characteristics.